2018
DOI: 10.1111/phen.12252
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia affects survival to different oxidative stressors dependent upon the genetic background in Drosophila melanogaster

Abstract: It is well known that the rate of ageing varies among individuals dependent on the genetic background. In the present study, we explore how Wolbachia infection (a common insect endosymbiont bacterium) and oxidative stress interact in ageing with respect to two different genetic backgrounds of Drosophila melanogaster. Naturally infected and cured lines of Drosophila are challenged with either paraquat or l‐arginine to generate two different types of oxidative stress. We first observe that removing Wolbachia inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Perhaps the variation in bacterial load among different types of Wolbachia infection partly explains the diversity in the effects they caused in the host. Such a correlation between Wolbachia titre and cytoplasmic incompatibility was discovered earlier in the parasitoid wasp Asobara japonica and the mosquito Aedes albopictusi (Kraaijeveld et al, 2011;Calvitti et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Perhaps the variation in bacterial load among different types of Wolbachia infection partly explains the diversity in the effects they caused in the host. Such a correlation between Wolbachia titre and cytoplasmic incompatibility was discovered earlier in the parasitoid wasp Asobara japonica and the mosquito Aedes albopictusi (Kraaijeveld et al, 2011;Calvitti et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…females. It was shown earlier that the effect of Wolbachia on host fitness and stress resistance is dependent on the genomic background of the Drosophila lineage (Fry et al, 2004;Capobianco et al, 2018). Based on these data, Capobianco et al 2018concluded that the effect of Wolbachia on fitness is unpredictable across the individual genetic backgrounds of host animals.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to address whether the cyto-nuclear interactions observed in our study were mediated primarily by heterogeneity in the Wolbachia infection status of the populations, since Wolbachia has been observed to positively or negatively influence lifespan outcomes across previous studies (Fry & Rand, 2002;Fry et al, 2004;Alexandrov et al, 2007;Capobianco et al, 2018), or by sequence divergence in the mitochondrial genome, across the cyto-nuclear populations. To this end, we were able to address two questions.…”
Section: Discussionmentioning
confidence: 99%
“…The Wolbachia endosymbiotic bacterium has been shown to exert influences on the biology of its hosts, ranging from pronounced effects on the phenotype such as cytoplasmic incompatibility (CI) in some arthropod species, to neutral or minor manipulations of cellular and reproductive processes; effects hypothesized to have evolved because they increase the relative fitness of Wolbachia-infected individuals within a population (Zug & Hammerstein, 2015;Correa & Ballard, 2016). Wolbachia has also been demonstrated to influence other host phenotypes such as lifespan and survival outcomes (Fry & Rand, 2002;Fry et al, 2004;Alexandrov et al, 2007;Maistrenko et al, 2016;Capobianco et al, 2018). Furthermore, other evidence has suggested that the magnitude of effects of Wolbachia infection on host phenotype can change across the nuclear genetic background of their hosts (Fry & Rand, 2002;Fry et al, 2004;Capobianco et al, 2018), implying that epistatic interactions between Wolbachia and their hosts may contribute to the host phenotypic expression (Correa & Ballard, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation